Faktor-faktor yang Mempengaruhi Mahasiswa Ekonomi Syariah Universitas Sultan Ageng Tirtayasa Tetap Menggunakan Bank Konvensional - Ani Aliani; Melandri Ilhan Wardhana; Salma Nasywaa Zhafiroh; Ahmad Jaelani; PRATAMA, AMELIA (Yayasan Penelitian dan Pengabdian Masyarakat Sisi indonesia, 2024)
The use of conventional banks by Sharia Economics students at Sultan Ageng Tirtayasa University is still interesting to study, even though their understanding of Islamic banking is good. This study aims to identify factors that influence the interest of Sharia Economics students in using conventional banks. The research method used is quantitative with data collection through questionnaires distributed to 122 students. The data were analyzed using multiple linear regression to determine the effect of independent variables on student interest. The results showed that ease of access, service quality, and habit are the main factors influencing students' decisions in choosing conventional banks. In addition, social and economic factors also contributed significantly. The findings are expected to provide insights for Islamic banking to improve services and marketing strategies to attract more students. Keyword: Conventional Banks, Student Interest, Islamic Economics, Influencing Factors.